Pendekatan Filosofis dalam Pengembangan Layanan Bimbingan dan Konseling di Era Revolusi Industri : Internet of Things (IoT) - Ardini, Fadhila Malasari; Jannah, Miftahul; Widiatmoko, Mualwi (Universitas Mathla'ul Anwar Banten, 2025)
The rapid advancement of technology, particularly the Internet of Things (IoT), has significantly influenced the field of guidance and counseling services. IoT enables counselors to adopt innovative methods, such as online counseling applications, chatbots, virtual reality (VR), augmented reality (AR), and mixed reality (MR), to reach a broader audience. Despite these advancements, the human role of counselors remains vital due to the importance of empathy and emotional sensitivity in the counseling process.A philosophical approach is crucial to establish ethical and humanistic foundations for the development of technology-based guidance and couseling services. This approach emphasizes respect for human values, professional ethics, and social responsibility. Technology should act as a supporting tool, not a replacement, in fostering meaningful relationships between counselors and clients.With proper integration, technology-based guidance and counseling services can enhance counseling effectiveness, expand accessibility, and create more personalized and holistic experiences, empowering individuals to navigate the challenges of the Fourth Industrial Revolution.